2014
DOI: 10.1590/s0100-54052014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Reação de genótipos de algodoeiro à mancha-de-alternária

Abstract: RESUMOPalavras-chave adicionais: Gossypium hirsutum L., Alternaria macrospora, resistência genética.Em três experimentos de campo, realizados em Cambará-PR e Londrina-PR, no ano agrícola 2011/12 e em Piracicaba-SP no ano 2012/13, e sob ocorrência natural do patógeno, foi avaliada a reação de 12 genótipos de algodoeiro à incidência da mancha-de-alternária (Alternaria macrospora). Diferenças altamente significativas entre os genótipos foram observadas nas três localidades, dando margem à formação de três, quatro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Several authors have described the resistance and susceptibility of cotton to Ramularia leaf spot (Lima et al, 2010;Cia et al, 2008Cia et al, , 2014. In this study, were observed significant interactions between genotype and chemical fungicide and biofungicide treatments.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Several authors have described the resistance and susceptibility of cotton to Ramularia leaf spot (Lima et al, 2010;Cia et al, 2008Cia et al, , 2014. In this study, were observed significant interactions between genotype and chemical fungicide and biofungicide treatments.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the genotypend FMT 709 was resistant to two Ramularia isolates (IMA 244 and IMA 237) and that the genotypes BRS 336 and IAC 08 2031 were susceptibles (Table 1). Cia et al (2008Cia et al ( , 2014 observed that these three genotypes (i.e., IAC 08 2031, FMT 709, and BRS 336) were resistant. Therefore, as these results indicate, it is important to examine several isolates of R. aureola in the selection of germplasm (Girotto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os danos causados pelo patógeno podem ser de até 20% quando a cultivar é susceptível ao fitopatógeno (CIA et al, 2014). Nesse trabalho, foi encontrado esse patógeno em crotalaria coletada na Fazenda Mutum, sendo que esta faz cultivo de algodão em sua área.…”
Section: Resultados E Discussõesunclassified